METHODS OF DEVELOPMENT OF PHYSICAL AND TACTICAL SKILLS OF STUDENTS OF CONTRACT MILITARY EDUCATION ON THE BASIS OF ACMELOGICAL APPROACH (Scientific journal of the Fergana State University, 2023)
qwerwqerwqe